Management of Tri Nur Vocational and Training Institute in Gorontalo City: Manajemen Lembaga Ketrampilan dan Pelatihan Tri Nur Kota Gorontalo - Maryam Podungge; Yahya Antu; Tety Thalib (Journal of Management Specialists, 2024)
This research aims to investigate and provide an objective assessment of the management of Tri Nur Skills and Training Institute in Gorontalo City, with a specific focus on planning, implementation, and evaluation. The research utilizes a descriptive qualitative approach, employing data collection techniques such as observation, interviews, and the recording of secondary data. Following the research type, data analysis involves data reduction, presentation, and drawing conclusions. The findings indicate that the management of Tri Nur Skills and Training Institute in Gorontalo City exhibits suboptimal performance in terms of planning. The identification of learning needs for participants/citizens is limited to completing the biodata form. The implementation aspect also falls short of optimal, as traditional learning processes like private lessons are not effectively conducted. Participants struggle to comprehend the material, leading to additional explanations outside the classroom, a practice not consistently undertaken by the instructor. The evaluation process proves ineffective, failing to meet the set targets or graduation standards aligned with the Indonesian National Work Competency Standards. Therefore, further research is necessary to enhance planning effectiveness, ensuring that all programs align with the intended goals and targets.